Clients’ experience and satisfaction of utilizing healthcare services in a community based health insurance program in Lahore, Bangladesh - Ariffin, Ahmad Azuhairi; Arshad, Junaid (Community Health Society Malaysia, 2020)
Background: The growing concept of Community Based Healthcare Insurance (CBHI) refers to the offerings of financial protection in contradiction of illness cost and enhancing the accessibility to quality healthcare services for the people who belong to rural low-income households and are often accepted from official insurance. The main aim behind carrying out this study was to assist concerned authorities in the healthcare sector of Pakistan regarding the implementation of quality enhancement initiatives of community-based health insurance programs. Materials and Methods: A mixed-method design was adopted where the structured questionnaire was used to collect primary. The sample comprised of 386 participants for the survey and 8 for interviews regarding their experiences and satisfaction towards the services offered and utilised under an insurance programme. The researcher approached two main hospitals of Lahore where the insurance programme has been engaged in offering services; these hospitals included Sharif Medical City Hospital and Punjab Institute of Cardiology. The researcher used descriptive statistics and multinomial regression for quantitative assessment. For qualitative assessment, thematic analysis was used on the basis of responses obtained from interviews. Result: The findings of the study concluded that patients were satisfied with the services provided at the hospitals chosen as the study setting. The hospitals under the insurance programme in Lahore have been engaged in providing a relaxed environment and it has affected the experience and satisfaction of the patients towards the services. Conclusion: Patients are getting their desired healthcare results under the insurance programme, and are contented with the overall healthcare service. The experience of clients who consumed health insurance program embraces great importance in the improvement of further improving healthcare services and for designing effective healthcare policies.